2021
DOI: 10.21203/rs.3.rs-506145/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the feasibility and effectiveness of e- OSCE in the COVID- 19 era

Abstract: Background: The emergence of coronavirus disease 2019 (COVID-19) and its quick progress to a global pandemic has urged medical schools to shift from didactic to distance learning and assessment approaches. The quality of clinical training and assessment have been jeopardized due to the regulatory restrictions and potential hazards to human lives. The aim of this paper is to evaluate the feasibility and effectiveness of an electronic Objective Structured Clinical Examination (e-OSCE), which attempted to transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…Once the candidate-patient encounters were complete, candidates filled in their post encounter notes and were placed back into the main Zoom room, and the process repeated for the next case [ 60 , 63 ]. Other studies reported using similar functions in Microsoft Teams [ 37 , 52 , 62 , 68 , 71 ], where candidates remained in a ‘channel’ while simulated patients and examiners rotated between candidates. (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Once the candidate-patient encounters were complete, candidates filled in their post encounter notes and were placed back into the main Zoom room, and the process repeated for the next case [ 60 , 63 ]. Other studies reported using similar functions in Microsoft Teams [ 37 , 52 , 62 , 68 , 71 ], where candidates remained in a ‘channel’ while simulated patients and examiners rotated between candidates. (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There was considerable variation between studies in the approach to patient participation in stations. Four studies described holding examinations without real or simulated patients [ 37 , 53 , 57 , 66 ]; examiners asked candidates questions based on sequential images or laboratory results shared with the candidate using the ‘share-screen’ function of Zoom [ 53 ], or Microsoft Teams [ 37 , 62 ]. In addition, candidates were questioned on what they would then ask patients in their history to formulate a diagnosis [ 37 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is happened due to unawareness of covid-19 and took unpredictable time to cure purely (transition time). The transition can be decomposed into several interconnected dimensions that impact the feasibility and the quality of the distance learning provided [10] [11].…”
Section: Introductionmentioning
confidence: 99%